Teacher training and professional identity: the contribution of collaborative work in education - Gonçalves, Daniela Ramos (2019)
Within the scope of teacher training, we present the perception of students who attend the masters of arts in teaching about the contribution of collaborative work networks in the process of creating their professional identity. The data collected from reflective narratives on which we focused reflect the perceptions of 44 students after their first experience of supervised teaching practice, which we consider to be elucidative of a true network work. The content analysis of the narratives focuses on five levels of analysis: i) role of Higher Education supervising teachers in the implementation of Supervised Teaching Practice (STP); ii) role of cooperative counsellors in the implementation of STP; iii) acquisition / development of competences related to the professional, social and ethical dimension; iv) acquisition / development of competences regarding the dimension of school participation and the relationship with the community; and (v) acquisition / development of reflective skills on the practice of teaching. We believe this work to be a constructive process in the sense that the trainee sets himself up as a professional through the way he reflects, autonomously, but also from the dialogical reflection either with the pedagogical pair / group from the teacher training institution, or with the supervisor and cooperative counsellor, in the context of the educational community in which he/she operates.